Apparent Motion Is Computed in Perceptual Coordinates. (July 2020) - Hui, Jiahan; Wang, Yue; Zhang, Peng; Tse, Peter U.; Cavanagh, Patrick
When a Gabor moves in one direction in the visual periphery while its internal texture moves in the orthogonal direction, its perceived direction can deviate from its physical direction by as much as 45° or more. Lisi et al. showed that immediate saccades go to the physical location of double-drift targets, whereas delayed saccades primarily go to their perceived locations. Here, we investigated whether the apparent motion seen from the offset of a double-drift stimulus to the onset of a later target probe originates from the perceived or physical location of the double-drift stimulus. We find that apparent motion proceeds away from the perceived position of the double-drift stimulus at all temporal delays. This suggests that apparent motion is computed in perceptual rather than retinotopic coordinates.